Effect of hot isostatic pressing on the microstructure and fracture toughness of laser additive-manufactured MoSiBTiC multiphase alloy. (November 2020) - Zhou, Weiwei; Tsunoda, Kengo; Nomura, Naoyuki; Yoshimi, Kyosuke
Abstract: MoSiB-based alloys are extremely promising ultrahigh–temperature materials, owing to their high melting points, good thermal stability, and excellent elevated-temperature mechanical properties. However, their fabrication is limited to conventional manufacturing techniques. In this work, a MoSiBTiC multiphase alloy, mainly consisting of Mo solid solution (Moss ), Mo5 SiB2 (T2 ), and TiC phases, was fabricated by laser powder bed fusion (L-PBF) using ball-milled alloy powders; subsequently, the effect of hot isostatic pressing (HIP) on its microstructure and fracture toughness was investigated. Due to the non-equilibrium metallurgical characteristics of L-PBF, the as-built alloy included uniform and fine-grained structures, as well as internal microcracks. The length of microcracks was effectively reduced with the assistance of the TiC bridging effect during HIP. As revealed by a high-resolution transmission electron microscope, the TiC was uniformly dispersed and was in close contact with the Moss or T2 phase. Consequently, the MoSiBTiC multiphase alloy exhibited a high fracture toughness of 9.0 MPa(m) 1/2 after HIP at 1973 K. This work could be an important step towards the fabrication of high-performance refractory components with advanced properties in ultrahigh–temperature use. Graphical abstract: Unlabelled Image Highlights: A high-performance MoSiBTiC alloy was designed by laser powder bed fusion (L-PBF) and hot isostatic pressing (HIP). L-PBF process was optimized to fabricate a MoSiBTiC alloy using ball-milled powders. Microstructural evolution during HIP was observed via high-resolution TEM. TiC phase acted as a healing agent for repairing internal microcracks.